Deformation and Failure of Supported Five-Fold Twinned Silver Nanowires under Tensile, Compressive, and Cyclic Loading - Moninger, Marco; Vogl, Lilian; Schweizer, Peter; Denninger, Peter; Smolka, Patricia; Will, Johannes; Spiecker, Erdmann (ACS nano, 2025)
Silver nanowire (AgNW) networks have emerged as one of the most promising materials for flexible transparent conductive electrodes. These wires offer excellent electrical, optical, and mechanical properties and can be applied using low-cost printing techniques with the potential for upscaling. To elucidate the mechanical properties of nanowire networks for use in flexible electronics, it is essential to first characterize the behavior of individual wires adhered to the polymer surface under mechanical loading of the polymer. This study investigates the mechanical response of isolated nanowires during uniaxial in situ tensile testing of the polymer using correlative microscopy, which combines the advantages of light and electron microscopy. By changing the orientation of the nanowires with respect to the tensile straining axis of the polymer, the nanowires experience either tensile (for parallel orientation) or compressive forces (for perpendicular orientation) according to the polymer’s elastic–plastic Poisson’s ratio, which links lateral contraction of the polymer to tensile strain. Aligned and isolated AgNWs were applied to flat surfaces of two polymers, PET and PDMS, which serve as model systems to investigate the effect of the substrate on the mechanical response of the nanowires. We observe a strong influence of the polymer type on the wire deformation behavior and fracture, which we attribute to the different adhesion strength of the wires on PET and PDMS. While the wires on PET undergo multiple fractures, breaking into segments of roughly equal length under tensile loading, those on PDMS typically fracture only once, accompanied by early sliding of the wire on the substrate. Compression tests revealed localized plastic deformation by nanowire kinking with the formation of new grain boundaries for both polymer substrates. Electron microscopy studies revealed different deformation configurations depending on the amount of load applied. In addition, cyclic compressive tests provided insight into the fatigue behavior of the wires. Here, newly formed grain boundaries acted as potential fracture sites, whereas the purely elastic deformation remained fully reversible up to 1000 cycles.
CRIS-Team Scopus Importer:2025-09-12
Keywords: correlative light and electron microscopy; flexible transparent electrode; mechanical testing; nanowire deformation and failure; silver nanowire